Method of converting the monolithic architecture of a Front-End application to microfrontends - Nikulina, Olena Mykolaivna; Khatsko, Kyrylo Olexandrovych (Національний технічний університет "Харківський політехнічний інститут", 2023)
Web systems have existed for a long time and quite a lot of them have been created. Modern development uses new microservice architectural to improve performance, portability, and other important characteristics. This necessitates the transformation of legacy systems from a monolithic architecture to a microservices one. Such a process is complex and costly, so improving the methods for converting old systems to a new platform is relevant. This research aims to develop a method of applying microfrontends approach for monolithic single page applications (SPA). The article proposes a method of transforming the software system architecture from monolithic to microservice architecture (MSA). Since the client part of the system is considered, the term microfrontend is proposed, as an analog of microservers in the server part of the software systems. A brief review of existing architecture reengineering research is made and the advantages of a microservice approach are identified. The proposed three-stage method differs from the methods by the selection of an additional stage of conversion, which allows to gently change the connections between parts of the monolithic application, which were implemented in the initial monolithic architecture. The first stage is reverse engineering, it is proposed to shift the focus from the search for outdated code to the functional analysis of the program as such. The second stage, a transition to a modular architecture with the allocation of functionality into separate modules is proposed. At the end of the third stage, we have several separate programs (microinterfaces) that are connected to the main program. An experiment with a typical external SPA demonstrates the operation of the proposed algorithm. The system obtained as a result of the transformation is compared with the original one according to the following measurable parameters: production builds building time, size of the main bundle, and first page average load time. All comparisons showed the advantages of the system obtained as a result of the conversion. As a result, the architecture transformation algorithm allows you to obtain a guaranteed better result, taking into account the limitations of the interface SPA, which were not considered by the authors of previous articles.

Вебсистеми існують давно і їх створено досить багато. В сучасній розробці використовуються нова архітектура мікросервісів для підвищення продуктивності, переносимості та інших важливих характеристик. Це зумовлює необхідність трансформації застарілих систем від монолітної архітектури до мікросервісної. Процес трансформації складний і дорогий, тому удосконалення методів перетворення старих систем на нову платформу є актуальним. Це дослідження спрямоване на розробку методу трансформації для монолітних односторінкових програм (SPA). У статті запропоновано метод трансформації архітектури програмної системи від монолітної до мікросервісної архітектури (MSA). Оскільки розглядається клієнтська частина системи, пропонується термін мікрофронтенд, як аналог мікросерверів у серверній частині програмних систем. Зроблено короткий огляд існуючих досліджень реінжинірингу архітектури та визначено переваги мікросервісного підходу. Запропонований метод з трьох етапів відрізняється від інших методів виділенням додаткового етапу перетворення, що дозволяє м’яко змінювати зв'язки між частинами монолітного додатку, які були реалізовані в початковій монолітній архітектурі. Перший етап – реверсінжиніринг, пропонується перенести фокус з пошуку застарілого коду на функціональний аналіз програми як такої. На другому етапі пропонується перехід до модульної архітектури з виділенням функціоналу в окремі модулі. Наприкінці третього етапу ми маємо кілька окремих програм (мікроінтерфейсів), які підключаються до основної програми. Експеримент із типовим зовнішнім SPA демонструє роботу запропонованого алгоритму. Система, що отримана в результаті трансформації, порівнюється з вихідною за такими вимірюваними параметрами: час створення виробничих збірок, розмір основного пакету, що надсилається в браузер, та середній час завантаження першої сторінки. Усі порівняння показали переваги системи, отриманої в результаті перетворення. У результаті алгоритм трансформації архітектури дозволяє отримати кращий результат, враховуючи обмеження інтерфейсного SPA.
Метод перетворення монолітної архітектури Front-End додатку на мікрофронтенди
Keywords: information system; software architecture; algorithm; monolith model of an information system; software development process; software migration; microservice architecture; single page application; method of converting to microfrontends; інформаційна система; архітектура програмного забезпечення; алгоритм; монолітна модель інформаційної системи; процес розробки програмного забезпечення; міграція програмного забезпечення; мікросервісна архітектура; односторінковий додаток; метод перетворення на мікроінтерфейси